Upaya Pemerintah Desa Karangsari, Cluwak-Pati Dalam Menyemai Sikap Toleransi Dikalangan Masyarakat - Hasan Bastomi; Salma Lathifatun Nisa’ (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to reveal the efforts of the Karangsari Village government in sowing the attitude of community tolerance. The research on the efforts of the Karangsari Village government in sowing the tolerance attitude of the community was carried out using a qualitative approach with the type of field research (field research) with data collection techniques using Interview, Observation and Documentation Techniques. The research subjects or informants in this research are the Village Head and Religious Leaders of Karangsari Village. The results of the study indicate that the efforts of the Karangsari Village government in cultivating an attitude of tolerance with various efforts, namely by: (1) Efforts to maintain community unity by prioritizing community unity have long been conditioned by mutual assistance and respect between the community. (2) Efforts to cultivate an attitude of mutual respect, namely by greeting each other and not alienating other religions, participating in every activity carried out by the community, and not insulting other religions. (3) Efforts through religious activities, namely by inviting each other when there are religious activities but not participating in worship of other religions and helping each other and mutual cooperation in inter-religious activities. (4) There are no inhibiting factors in efforts to sow tolerance in the Karangsari Village community because all communities and government all complement each other and inter-religious communities respect, motivate, remind and respect each other. While the supporting factors in efforts to sow tolerance in the Karangsari Village community are the figures in the Karangsari village often meet and coordinate in maintaining tolerance between the people and their communities which are easy to regulate and the community has a high tolerance spirit that is embedded in the soul.